P5 4 Earth’s Oven - Sanjeevvijay, Shaswathan; Munt, Leon; Iordanidis, George (Physics Special Topics, 2024)
In this paper, we determine the initial velocity that a whole chicken refrigerated to 5 °C would require if it were dropped through the Earth as an unconventional cooking method. When dropped with zero initial velocity the chicken reaches 821 °C, causing it to burn. To prevent overcooking, the chicken is found to need an initial velocity of 50 kms−1 raising the internal temperature of the chicken to 91 °C, an ideal temperature for cooking